Model-aided catalyst design, optimization and analysis - Yan, Wenjin (2013)
Catalyst, a material that can affect the rate of a reaction without being changed itself, plays an important role in chemical industry worldwide. Currently, the development of catalysts is based on experiments under the guidance of experience and intuition of chemists. Some chemists follow one-factor-at-a-time (OFAT) method, however, OFAT was proved to be suboptimal. As a result, the main objective of my study is to achieve rational model-based catalyst design and optimization. The basic part of this framework is response surface methodology (RSM), a combination of (1) design of experiments (DoE), (2) development of a data-based model and (3) model-based optimization. Based on this framework, other approaches may be combined to meet different requirements.